Long-Duration Energy Storage: A Critical Enabler for Renewable Integration and Decarbonization - Yuyang Zeng; Tuo Zhou; Tong Wang; Man Zhang; Shuping Zhang; Hairui Yang (Energies)
This paper focuses on the critical role of long-duration energy storage (LDES) technologies in facilitating renewable energy integration and achieving carbon neutrality. It presents a systematic review of four primary categories: mechanical energy storage, chemical energy storage, electrochemical energy storage, and thermal energy storage. The study begins by analyzing the technical advantages and geographical constraints of pumped hydro energy storage (PHES) and compressed air energy storage (CAES) in high-capacity applications. It then explores the potential of hydrogen and synthetic fuels for long-duration clean energy storage. The section on electrochemical energy storage highlights the high energy density and flexible scalability of lithium-ion batteries and redox flow batteries. Finally, the paper evaluates innovative advancements in large-scale thermal energy storage technologies, including sensible heat storage, latent heat storage, and thermochemical heat storage. By comparing the performance metrics, application scenarios, and development prospects of various energy storage technologies, this work provides theoretical support and practical insights for maximizing renewable energy utilization and driving the sustainable transformation of global energy systems.